Dialysis Access, Infections, and Hospitalisations in Unplanned Dialysis Start Patients: Results from the Options Study. Issue 2 (February 2017) - Machowska, Anna; Alscher, Mark D.; Vanga, Satyanarayana Reddy; Koch, Michael; Aarup, Michael; Qureshi, Abdul R.; Lindholm, Bengt; Rutherford, Peter
Introduction: Unplanned dialysis start (UPS) associates with worse clinical outcomes, higher utilisation of healthcare resources, lower chances to select dialysis modality and UPS patients typically commenced in-centre haemodialysis (HD) with central venous catheter (CVC). We evaluated patient outcomes and healthcare utilisation depending on initial dialysis access (CVC or PD catheter) and subsequent pathway of UPS patients. Methods: In this study patient demographics, access procedures, hospitalisations, and major infectious complications were analysed over 12 months in 270 UPS patients. PD technique survival and impact of switching from HD to PD was examined along with logistic regression to investigate factors predicting AV fistula formation. Results: 72 UPS patients started with PD catheter and 198 with CVC. PD patients were older and more comorbid but had a significantly lower number of access procedures while there was no difference in hospitalisation or major infections. 13/72 initial PD patients switched to HD and 1-year technique survival was 79%. 158/198 patients remained on HD and 73/158 reported permanent access formation. Older age, OR = 0.34 (CI, 0.17-0.68) and cardiac failure, OR = 0.31(CI, 0.13–0.78), were significant negative predictors of receiving fistula. Younger patients, OR = 0.29 (CI, 0.11–0.79) and those who received AVF, OR = 0.11 (CI, 0.03–0.38), had significantly lower odds of death. Discussion: UPS with initial PD was possible in many patients and was associated with lower requirement for access procedures. AVF formation in UPS patients starting on HD was associated with better 1-year survival. Modality switching in UPS patients requires careful clinical management, including clinical practice patterns promoting permanent HD access formation.